Gender issues that emerge in pedagogical experiences with children's pranks and games in early childhood education: teachers' perspectives in a municipality in the south of Minas Gerais State. (Research, Society and Development, 2022)
This research aims to investigate gender issues in Early Childhood Education, starting from pedagogical experiences that emerge in the use of games in Physical Education classes by teachers. The present study is justified, since it is important to reveal in which everyday situations conflicts and inequalities between boys and girls arise within educational institutions. Part of the Physical Education teachers working in Early Childhood Education in a municipality located in the south of Minas Gerais contributed to the realization of this investigation, while we used semi-structured interviews to produce empirical material (teacher narratives) that responded to the problem posed. In order to interpret the utterances of the teachers, a qualitative approach was used for the elaboration of thematic categories through content analysis. As a result, it was possible to observe that the teachers' perceptions regarding gender issues, in the context of games and games, followed some paths, namely: 1) that boys and girls do not create problems and conflicts concerning gender boundaries in the context of games and games, in effect, they manage to live and interact with a certain harmony 2) teachers conceive that coeducational practices favor the constitution of equitable sociability between boys and girls, albeit with a naturalized, normalized and essentialized discourse.